Colombia’s ‘Misión Rural’ and CIAT: allies to transform Colombian agriculture - International Center for Tropical Agriculture (2014)
As the third largest and one of the fastest growing economies in Latin America, Colombia has the capacity to influence the socioeconomic well-being of the entire region. Nevertheless, Colombia has yet to fulfill its potential for productivity and competitiveness on the global stage, and rural underdevelopment is accompanied by high rates of poverty (46.1%) and extreme poverty (22.1%). ‘Misión Rural’ is the Colombian government’s road map for the agricultural sector over the next 20 years, aiming to achieve equitable distribution of the fruits of economic growth by supporting rural development, ensuring the provision of public goods for rural areas, and effecting modern and efficient institutionalization. The International Center for Tropical Agriculture (CIAT), as part of the largest global agricultural research partnership, has the experience, technologies, networks, and methodologies to contribute to the goals of Misión Rural, specifically through: 1) improving links between smallholder farmers and the wider market, 2) addressing climate change adaptation and mitigation, 3) implementing efficient, site-specific agriculture, 4) supporting land management planning through modeling and scenario building, and 5) managing knowledge and development with participatory processes.